Behavioral, biochemical, immune, and histological responses of Nile tilapia (Oreochromis niloticus Linnaeus, 1758) to lead, mercury, and pendimethalin exposure: individual and combined effects - Rasha M. Reda; Eman M. Zaki; Ahmed A. A. Aioub; Mohamed M. M. Metwally; Aya M. Yassin; Fatma Mahsoub (Environmental Sciences Europe)
Abstract The aquaculture sector is facing environmental issues because of rising chemical pollution of aquatic systems, which may be caused by man-made or natural causes. The combined action of these mixtures can produce an effect that is either severalfold higher or severalfold lower than the overall toxicity of the individual components. The objective of this study is to evaluate the impact of three individual toxicants: lead (Pb 0.088 mg L−1), mercury (Hg 0.084 mg L−1), and pendimethalin (PM 0.355 mg L−1) and their combinations on the behavior, oxidative stress, immunology, biochemistry, and histopathological changes in Nile tilapia. The results show that mortality was evident across all treatment groups and was highest in the mixture (MIX) group, at 33.4%. Some of these behavioral changes included increased mucus secretion, fin rot, and dark skin coloration of the fish, all of which were evidently exacerbated in the MIX group. The erythrocyte and hemoglobin indices presented marked reductions in the MIX and PM groups in comparison to the control group. The MIX group had higher levels of serum creatinine and urea, as well as the liver enzymes alanine aminotransferase, aspartate transaminase, and alkaline phosphatase. They also had higher levels of malondialdehyde and lower levels of total antioxidant capacity, which showed oxidative stress. The stress biomarkers, cortisol and glucose, showed greater impact on the MIX and PM groups. The neurobehavioral assessment demonstrated noticeable decreased acetylcholinesterase levels in PM and MIX-exposed groups. In the serum immunological parameters, levels of nitric oxide and lysozyme were lower, especially in the MIX and PM groups. In all experimental groups, especially the MIX group, the levels of spleen pro-inflammatory cytokine genes were higher. The histopathological examination revealed marked lesions in the gills, liver, and brains in the form of inflammation, necrosis, and circulatory alterations. Among the exposed groups, the MIX group exhibited the highest histopathological changes. Collectively, our findings demonstrated significant toxic effects of heavy metals and herbicides on Nile tilapia, revealing a synergistic impact on both physiological and histopathological responses resulting from combined exposures. The data evidently indicate the ecological hazards associated with heavy metals and herbicides in aquatic ecosystems.